2014
DOI: 10.1186/s12915-014-0084-2
|View full text |Cite
|
Sign up to set email alerts
|

The comprehensive analysis of DEG/ENaC subunits in Hydrareveals a large variety of peptide-gated channels, potentially involved in neuromuscular transmission

Abstract: BackgroundIt is generally the case that fast transmission at neural synapses is mediated by small molecule neurotransmitters. The simple nervous system of the cnidarian Hydra, however, contains a large repertoire of neuropeptides and it has been suggested that neuropeptides are the principal transmitters of Hydra. An ion channel directly gated by Hydra-RFamide neuropeptides has indeed been identified in Hydra – the Hydra Na+ channel (HyNaC) 2/3/5, which is expressed at the oral side of the tentacle base. Hydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 54 publications
(78 reference statements)
2
61
0
Order By: Relevance
“…In a recent report (Assmann et al, 2014), the seven additional DEG/ENaC subunits from Hydra magnipapillata shown in Fig. 10 have been functionally characterized and the results support their role in neuromuscular transmission.…”
Section: Note Added In Proofmentioning
confidence: 72%
“…In a recent report (Assmann et al, 2014), the seven additional DEG/ENaC subunits from Hydra magnipapillata shown in Fig. 10 have been functionally characterized and the results support their role in neuromuscular transmission.…”
Section: Note Added In Proofmentioning
confidence: 72%
“…Electrophysiological measurements were conducted as previously described3042 by expression of ASICs in stage V and VI oocytes of Xenopus laevis . Oocytes were surgically removed under anaesthesia (4 g l −1 tricaine methanesulfonate for 20–30 min) from adult Xenopus laevis females.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to FaNaC, HyNaC is an unselective cation channel with a high Ca 2+ permeability (Dürrnagel et al, 2012) (Table 2). Soon after, all 12 DEG/ENaCs of Hydra were cloned, and it was shown that Hydra likely contains at least six different functional HyNaCs (Assmann et al, 2014). All are heterotrimers consisting of three different subunits activated by Hydra-RFamides I and II, and all are unselective cation channels (Assmann et al, 2014) (Table 2).…”
Section: Measuring Neuropeptide Levelsmentioning
confidence: 99%
“…Soon after, all 12 DEG/ENaCs of Hydra were cloned, and it was shown that Hydra likely contains at least six different functional HyNaCs (Assmann et al, 2014). All are heterotrimers consisting of three different subunits activated by Hydra-RFamides I and II, and all are unselective cation channels (Assmann et al, 2014) (Table 2). It is not clear why Hydra evolved such a variety of peptide-gated channels with similar properties, but differential targeting and ligand affinity are two possibilities.…”
Section: Measuring Neuropeptide Levelsmentioning
confidence: 99%